2018
DOI: 10.1002/ejoc.201801276
|View full text |Cite
|
Sign up to set email alerts
|

Glutarimide Alkaloids Through Multicomponent Reaction Chemistry

Abstract: A concise four step synthetic route for glutarimide alkaloids of high biological interest is presented. The scaffold is accessed via an Ugi four component reaction, hereby introducing two points of variation. This is followed by a hydrolysis, a cyclization under mild conditions, and an amine deprotection. The diastereomers of the cyclized intermediate can be easily separated, thus leading to optically pure alkaloids. By this route, four natural products and ten derivatives were synthesized. The scope and limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…In the literature, a large amount of information about approaches to the synthesis of (–)-julocrotine can be found. 47 Thus, in the publication of 2018 48 for the production of (–)-julocrotine and its analogues, a four-component Ugi reaction between (2-isocyanoethyl)benzene ( 58 ), isobutyric acid ( 59 ), methyl-4-oxobutanoate ( 60 ), and ( R )-1-(4-methoxyphenyl)ethanamine ( 61 ) was employed (Scheme 22 ). At the same time, it was found that the optimal conditions for this reaction are the use of 2,2,2-trifluoroethanol (TFE) as a solvent with a concentration of reagents of 1 mol/L.…”
Section: Multicomponent Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a large amount of information about approaches to the synthesis of (–)-julocrotine can be found. 47 Thus, in the publication of 2018 48 for the production of (–)-julocrotine and its analogues, a four-component Ugi reaction between (2-isocyanoethyl)benzene ( 58 ), isobutyric acid ( 59 ), methyl-4-oxobutanoate ( 60 ), and ( R )-1-(4-methoxyphenyl)ethanamine ( 61 ) was employed (Scheme 22 ). At the same time, it was found that the optimal conditions for this reaction are the use of 2,2,2-trifluoroethanol (TFE) as a solvent with a concentration of reagents of 1 mol/L.…”
Section: Multicomponent Reactionsmentioning
confidence: 99%
“…In the literature, a large amount of information about approaches to the synthesis of (-)-julocrotine can be found. 47 Thus, in the publication of 2018 48 for the production of (-)-julocrotine and its analogues, a four-component Ugi reaction between (2-isocyanoethyl)benzene (58), isobutyric acid (59), methyl-4-oxobutanoate (60), and (R)-1-(4-methoxyphe-…”
Section: Scheme 21 Synthesis Of a Drug Used Against Breast Cancer (Ag...mentioning
confidence: 99%
“…Multi-component reactions (MCRs) have regarded as essential tools for the preparation of biologically active heterocyclic compounds because of their productivity, convergence, simple procedures, and easy execution [ 1 ]. The development of MCRs and their applications for the one-pot synthesis of various useful heterocyclic compounds are of remarkable interest in the running research articles [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 Therefore, the design of novel MCRs has attracted great attention from synthetic organic chemists. [15][16][17][18][19][20] Chromenes and their fused analogues are a group of biologically active molecules occurring extensively in nature with a wide range of molecular modications. 21 Among them benzochromenes are one of the privileged scaffolds with a medicinal pharmacophore such as antibacterial, 22 antimicrobial, 23 antitumor, 24 and anti-inammatory.…”
Section: Introductionmentioning
confidence: 99%